Effect of Sheep’s Whey Edible Coatings with a Bioprotective Culture, Kombucha Tea or Oregano Essential Oil on Cheese Characteristics - Carlos D. Pereira; Hanna Varytskaya; Oliwia Łydzińska; Katarzyna Szkolnicka; David Gomes; Arona Pires (Foods)
Films and coatings based on biopolymers have been extensively studied in recent years since they have less impact on the environment, can be obtained from renewable sources, have good coating and film-forming capacity, are biodegradable and can have interesting nutritional properties. In the present study, sheep’s cheese whey powder (SCWP) was used to produce edible cheese coatings. Six types of cheese samples were produced: without coating (CON); treated with natamycin (NAT); with SCWP coating without antimicrobials (WCO); with SCWP coating with a commercial bioprotective culture (WFQ); with SCWP coating with kombucha tea (WKO); and with SCWP coating with oregano essential oil (WEO). At the end of the ripening period, all the cheeses were classified as full-fat and semihard, according to the Portuguese standard. The higher hardness and adhesiveness values of samples CON, WFQ and WKO were in line with the lower moisture in defatted cheese observed in these samples, indicating that future work should address the improvement of water vapor barrier properties of the whey-based coating. The samples treated with natamycin and with oregano essential oil presented significantly lower values for hardness. Differences were also observed on titratable acidity and aw, both between samples and because of ripening time. The color parameters of cheese samples also presented differences, chiefly in the rind, but the highest differences observed resulted from ripening time rather than between samples. In all cases, the counts of lactobacilli and lactococci surpassed log 7 CFU/g by the end of ripening. Regarding yeast and mold counts, the samples CON and WCO presented the highest values by the end of the ripening period (>log 4 CFU/g), while sample NAT presented the lowest value (ca. log 3 CFU/g). Samples WFQ, WKO and WEO presented values which were ca. 0.5 log cycles lower than samples CON and WCO. Hence, the use of SCWP alongside bioprotective culture, kombucha tea or oregano essential oil had a positive impact in the reduction of mold counts on cheese surfaces. Future work should also evaluate the joint use of different antimicrobials.